2012
DOI: 10.4067/s0717-97072012000400017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Experimental and DFT Studies on the Crystal Structure, Ftir, ¹h NMR and 13c NMR Spectra of Drivatives of Dihydropyridines

Abstract: Several derivatives of dihydropyridines are prepared through the condensation of aldehydes, dimedone and NH 4 OAc in H 2 O, in the presence of a catalytic amount of nano-Fe 3 O 4 . The crystalline products were characterized by FTIR, 1 H NMR and 13 C NMR. Density Functional Theory (DFT) calculations at the B3LYP level is used to optimize the geometries of isolated molecules, and to calculate the, FTIR, 1 H NMR and 13 C NMR spectra of selected synthesized compounds. We found that the DFT B3LYP calculated FTIR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These values agree with the reported range of 3300 to 2500 cm −1 , usually centered at 3000 cm −1 [53]. Finally, the weak band is probably due to the intramolecular hydrogen bond with a carbonyl group (ketone) [54]. Additionally, the C=O stretching intense band appearing at 1705 and 1611 cm −1 and 1703 and 1640 cm −1 are assigned to the carboxylic acid and ketone groups for 3a and 3b, respectively, which is consistent with the literature value, 1870-1540 cm −1 [53,55].…”
Section: Experimental and Theoretical Vibrational Spectrasupporting
confidence: 91%
See 2 more Smart Citations
“…These values agree with the reported range of 3300 to 2500 cm −1 , usually centered at 3000 cm −1 [53]. Finally, the weak band is probably due to the intramolecular hydrogen bond with a carbonyl group (ketone) [54]. Additionally, the C=O stretching intense band appearing at 1705 and 1611 cm −1 and 1703 and 1640 cm −1 are assigned to the carboxylic acid and ketone groups for 3a and 3b, respectively, which is consistent with the literature value, 1870-1540 cm −1 [53,55].…”
Section: Experimental and Theoretical Vibrational Spectrasupporting
confidence: 91%
“…The bands C7-H and C5-H at 2942 and 2935 cm −1 are presented as weak bands for 3a and 3b, respectively. In this case, Karthick et al [61] detected values in the span of 2979-2978 cm −1 for 1,4-dihydropyridines, Kavitha and Verlaj [62] detected values between 3144 and 2900 cm −1 for this band for isoxazoles; Radder et al [51] reported the value at 3029 cm −1 for a benzonitrile derivative; and Fekri and Nikpassand [54] reported values comprising 3077-2987 cm −1 for dihydropryridine derivatives. Related to C=O bands, two carbonyl groups are presented: C=O for the carbonyl of the acid moiety, which is displayed at 1738 cm −1 for 3a and 1730 cm −1 for 3b as medium bands.…”
Section: Experimental and Theoretical Vibrational Spectramentioning
confidence: 92%
See 1 more Smart Citation
“…2c confirm the grafting was successful based on the presence of the band at 1216 cm −1 , which originate from the C-N stretching of the grafting agents 52 . The band at 1540 cm −1 of the MIL-101-NO 2 is because of the stretching vibration of -NO 2 group 53 .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the Viola betonicifolia leaf extract contains biologically active phytomolecules that are particularly effective at destroying fungal strains. 57 Additionally, the superior antifungal activity of VB-Au NPs can be due to the synergistic impact of the nanoparticle's physical properties and the adsorbed biologically active phytomolecules from the leaves extract of Viola betonicifolia on their surface [31][32][33][34][35]. Balasubramanian et al, Dananjaya et al, and Jayaseelan et al have also reported effective antifungal activity of gold NPs synthesized using the extract of Jasminum auriculatum, Spirulina maxima, Abelmoschus esculentus, respectively, against different fungal strains.…”
Section: Antifungal Activity Of Green Synthesized Vb-au Npsmentioning
confidence: 99%